Boric acid toxicity trials on the wood borer Heterobostrychus aequalis waterhouse (Coleoptera: Bostrychidae) - Karam Singh, Daljit Singh; Abood, Faizah; Abdul Hamid, Hazandy; Ashaari, Zaidon; Abdu, Arifin (Science Publications, 2011)
Problem statement: The Heterobostrychus aequalis Waterhouse was a serious pest lumber of timber heveawood. The H. aequalis infest and tunnel along the wood grain, depositing eggs, which concomitantly turn into larvae and reduces the wood starch to a soft powder. The objectives of the study were to establish a suitable method for preservative trials on the wood borer and access the toxicity levels of boric acid for controlling the H. aequalis infestation. Approach: The voracious H. aequalis was collected from infested heveawood, mated and cultured on cassava. The adult beetles were exposed to boric acid treated cassava blocks as pilot trials. The boric acid concentration used was 1-5% including a control. Each treatment consists of five replicates. The voracious of H. aequalis generation was cultured for obtaining its freshly new emerged adult by exposing a number of H. aequalis directly from infested heveawood into artificial diet block and cassava. The mortality, weight loss of the test blocks, frass discharge duration and numbers of holes caused by H. aequalis were observed. Results: The results showed that the H. aequalis infested tended to penetrate the film after wrapping the heveawood with a layer of transparent cling film for 24 h experiment. The H. aequalis larvae stock cultured collected from infested heveawood exhibited differences in colour, activeness and aggression among males and females. The suitable test block size used was (2.0×5.0×1.5) cm3. The freshly emerged voracious of H. aequalis adults was more suitable than the larvae for boric acid toxicity trials. The 2% concentration was sufficiently killed the 4% boric acid treated test blocks. There was no hole observed on 5% boric acid treated test block and hence these concentrations were not infested by H. aequalis due to absence of frass in exposed blocks. Conclusion/Recommendations: There are noticeable physical and behavioural differences between voracious of H. aequalis collected from infested heveawood. The freshly emerged of H. aequalis adults were found suitable than the larvae as an indicator for determining the boric acid toxicity trials. The 5% of boric acid concentration was sufficient to control the infection of H. aequalis on heveawood. Further studies focusing on interaction between larvae, adults and population growth of H. aequalis with different hosts need to be carried out towards clarifying the predisposing factors that induce the infestation processes.